Evaluation of grassroots community–based legal aid activities in Uganda and Tanzania: Strengthening women’s legal knowledge and land rights - Peterman, Amber; Billings, Lucy; Behrman, Julia A. (International Food Policy Research Institute, 2013)
Progressive legislative actions in Uganda and Tanzania have improved women’s legal rights to land, however significant gender disparities persist in access, control, inheritance, and ownership of land at the grassroots level. One promising mechanism to improve the implementation of laws is through Community–based Legal Aid (CBLA) programs, which are typically designed as pro–poor to enhance legal empowerment of marginalized groups...A qualitative study of CBLA programs in Uganda and Tanzania was conducted by the International Food Policy Research Institute (IFPRI) to assess the efficacy of CBLA activities, understand challenges faced by CBLA implementing organizations, and document opportunities and potential for scaling–up.